SAT0582 Chagas' disease in patients with autoimmune diseases receiving immunosuppressive therapy. analysis of 48 cases. (15th June 2017) - Retamozo, S; Salinas, MJ Haye; Alvarellos, A; Saurit, V; Caeiro, F; Caeiro, JP; Carballo, V; Medeot, M; Salomone, O; Albertini, R; Merschon, F; Bonisconti, F; et al.
Abstract : Objectives: To analyze the main features at diagnosis and Chagas' Disease (CD) reactivation in patients with autoimmune diseases (AD) receiving immunosuppressive therapy (IT). Methods: 13 patients with AD diagnosed with CD admitted to our Units between January to December 2016. In addition, we performed a systematic analysis of cases reported to date through a MEDLINE search. Inclusion criteria 1) adults with AD treat with iT (glucocorticoids [GC], disease-modifying anti rheumatic drugs [DMARDs] and biological drugs [BD]); 2) had confirmed or were positive for 2 serological test for CD. Reviews, experimental studies, duplicate publications, and abstracts were excluded. Results: A total of 48 patients (13 from our Units and 35 from the literature search) fulfilled the inclusion criteria. There were 41 (85.4%) women, mean age of 43.8 years (range: 17–80). The main underlying disease was SLE in 22 (45.8%). Previous/current treatment at time CD diagnosis included GC >40mg/day in 27/48 (56.3%), DMARDs in 32/48 (66.7%) and 7 patients had previously received DB. CD was reactivated in 36 (75%) cases (mean 40.9 months [range: 0–252]) with the following patterns: high T. cruzi load by quantitative real-time polymerase chain reaction (qRTPCR) in 23 (63.8%) from which 20 (86.9%) had no clinical manifestation and 3 (13%) had panniculitis, the remaining 11 patients (30.5%) had positive XD with one of them had myositis, only one patient (2.7%) had fever. After a mean follow-up of 47 (range: 1–120) months, 4 patients with SLE died (8.3%), all had received GC>40mg/day, 3 had CD reactivation and all died due to SLE flare. No statistical differences were found with respect to CD diagnosis, use of GC, DMARDs, BD; in contrast, patients who had CD reactivation on therapy with GC >40mg/day showed higher cardiac involvement (83.3% vs 43.5%, p=0.03 OR 6.50 CI95% 1.15–36.57) where the time of immunosuppression in this group was lower in those who died median 0.53 (IQR 0.46–0.53) vs 3.00 (IQR 1.26–78.00) months, p=0.04. Patients with SLE and CD reactivation showed a higher risk of death (18.8% vs 0.0%, p=0.04, OR: 1.23, CI95% 0.97–1.57). Survival rate of the entire cohort was 91.5%. The poorest survival rates were observed in who had CD reactivation (log rank p=0.037). Conclusions: Reactivation was presented mainly as high T. cruzi load by qRTPCR without clinical manifestation of CD. Use GC>40mg/day showed a higher risk of CD reactivation with cardiac involvement. Considering this data it's reasonable to screen serologic and molecular tests before to start treatment with immunosuppressive drugs. Disclosure of Interest: None declared